A Consequence of Social Entrepreneurial Intent: The Good Life - Yang Zhang; Stephen McGuire
This study examines the relationship between personal dispositions, social entrepreneurial intent (SEI) and the good life in a sample of 2,000 college students in Los Angeles, Manila, Mexicali, Taipei and Yantai. Social cognitive career theory posits that a specific career choice$1 (Bin this case, becoming a social entrepreneur$1 (Baffects individuals$1 (Bexperience of a good life, and SEI mediates the relationship between personal dispositions and the good life. This article presents and empirically tests a broad conceptualisation of the good life$1 (Bgoing beyond happiness and satisfaction$1 (Bto include subjective and psychological well-being, freedom to make life choices, quality of social relations and pathways to reach goals. Extending the previous research, the study finds that the personal dispositions of trust, optimism, generosity and healthy life expectancy were robust predictors of SEI and that SEI mediated the relationship between personal dispositions and the good life. Finally, cultural context mattered; long-term orientation, low masculinity and high indulgence partially moderated the disposition-to-SEI-to-good life relationship.s